Metaverse as a Higher Education Tool: Notes From Musical Curricula at Early Childhood Education and Primary School Education Bachelor´s Degrees - Delegido, José Manuel Azorín; Guerrero Almagro, Berta; Rodríguez López, Marta (Harmonia: Journal of Arts Research and Education, 2024)
The use of the metaverse as an educational tool provides an immersive learning experience that gives students the chance to enter a virtual space that is perceived as a real-life environment. This study aims to examine how the metaverse can be a learning resource for engaging in music learning. Previous studies have set the metaverse as a potential means for higher education. Due to this, a concert hall with a symphonic orchestra in a performative set has been developed at a private university for the musical curricula included within the Early Childhood and Primary School Education Bachelor´s Degrees. Twenty recorded audio pieces in which the main instruments from the orchestra can be identified are also included. This investigation followed experimental, descriptive models, and 170 participants were involved. Results are similar to the evidence provided in the revised literature confirming the metaverse's value as an educational tool. It has been proven that being able to interact with the objects within the metaverse helps getting familiar with their characteristics. The surveyed students have confirmed that the metaverse is a useful learning resource as well as a suitable option for their future professional environment.